Implementation of Educational Technology in Thailand: A Comprehensive Study on Its Impact and Challenges - Preechasil, Ratchanok; Thamrongchai, Nattawut (International Journal of Education and Digital Learning (IJEDL), 2023)
The rapid advancement of technology has significantly transformed the education sector globally, with Thailand being no exception. This study aims to explore the implementation of educational technology in Thailand, focusing on the adoption of digital tools, platforms, and innovations that have reshaped the country's educational landscape. The study examines the benefits, challenges, and the effectiveness of educational technology in Thai schools and universities. By reviewing both qualitative and quantitative data collected from educators, students, and administrators, the research offers insights into how technological integration has affected teaching methodologies, student engagement, and academic outcomes. Furthermore, the paper addresses the barriers to successful technology adoption, such as infrastructural limitations, digital literacy gaps, and socio-economic disparities. This study provides recommendations for policymakers and educational institutions to enhance the integration of technology in Thailand's education system.